Effect of rare-earth dopants on the thermal behavior of tungsten–tellurite glasses - Ersundu, A. E.; Karaduman, G.; Celikbilek, M.; Solak, N.; Aydin, S. (Elsevier BV, 2010)
Abstract In the present study, the effect of rare-earth element addition on the thermal behavior of tungsten–tellurite glasses was investigated by running detailed differential thermal analyses. The glasses were prepared with the compositions of (1 −  x )TeO 2 – x WO 3 , where x  = 0.10, 0.15 and 0.20 in molar ratio and all three samples were doped with 0.5 and 1.0 mol% of Nd 2 O 3 , Er 2 O 3 , Tm 2 O 3 and Yb 2 O 3 . By applying different glass preparing methods, the effect of melt-quenching techniques on the thermal behavior of tellurite glasses was also investigated and almost the same thermal behavior was observed for all attempts. Therefore, the glass samples were obtained by heating high purity powder mixtures to 800 °C in a platinum crucible with a closed lid, holding for 30 min and quenching in water bath. In general, the addition of rare-earth elements to undoped samples affected the thermal behavior of tungsten–tellurite glasses by shifting the glass transition and exothermic reaction temperatures to higher values and increasing the thermal stability. Moreover, the introduction of rare-earth dopants significantly decreased the temperature values of the first endothermic peaks corresponding to the eutectic reaction; whereas a slight decrease was observed in the second endothermic peak temperatures representing the liquidus reaction. Addition of rare-earth elements with higher atomic number (Er 2 O 3 , Tm 2 O 3 and Yb 2 O 3 ) resulted in peak splitting of the eutectic reaction.